A highly conductive and robust anion conductor obtained via synergistic manipulation in intra- and inter-laminate of layered double hydroxide nanosheets. Issue 22 (18th May 2018) - He, Xueyi; Cao, Li; He, Guangwei; Zhao, Anqi; Mao, Xunli; Huang, Tong; Li, Yan; Wu, Hong; Sun, Jie; Jiang, Zhongyi
Abstract : Synergistic manipulation in intra- and inter-laminate of layered double hydroxide results in a highly conductive and robust anion conductor. Abstract : Layered double hydroxides (LDH), bearing trivalent cationic charge centers and hydroxyl slabs, hold great promise for use in efficient solid-state ion conductors. In this study, a composite membrane with ion-conducting 2D channels was prepared based on exfoliated LDH nanosheets and quaternized polyvinyl alcohol via a filtration process. The LDH laminates, which were formed by the stacking of exfoliated LDH nanosheets, primarily afforded the conductive performance of the membranes. Within the intra-laminate galleries of LDH, charge-balancing anions determined the channel size, water absorption capacity and electrostatic interactions inside the 2D channels. As a result, hydroxide ion transport was greatly affected by the anionic species present. The organic moieties inside the inter-laminate galleries of LDH conferred hydrogen bonds and covalent linkages at the organic–inorganic interfaces, resulting in a nacre-mimetic structure, leading to the improved mechanical properties of the composite membranes. The synergistic manipulation of composition and interactions within the intra- and inter-laminate galleries endowed the novel anion conductors with both high conductivity (156.3 mS cm −1 at 80 °C) and good mechanical performance (a tensile strength of 48.4 MPa and toughness of 2.09 MJ m −3 ).